Development of Accounting Through Automation and Artificial Intelligence - Claudiu BRÂNDAȘ; Ioan MINDA (CECCAR Business Review)

(untitled)
This paper explores the impact of automation and artificial intelligence (AI) on the field of accounting. As AI and automation technologies advance rapidly, they are transforming traditional accounting practices, shifting the role of accountants from routine, repetitive tasks to more strategic, value-added services. The integration of AI in accounting enhances processes like financial reporting, fraud detection, and cost analysis by automating labor-intensive tasks and providing real-time, data-driven insights. The paper discusses the transition from historical financial accounting to a more consultative role for accountants, supported by AI-driven analytics and predictions. It also highlights the need for accountants to adapt by developing new skills, particularly in data analysis, AI, and technology. Furthermore, the study underscores the critical need for responsible AI usage, emphasizing the importance of transparency, data security, and compliance with regulatory standards. The paper concludes by examining the implications of AI for accounting education, requesting curriculum updates to equip future professionals with the necessary skills to thrive in the evolving landscape of the accounting profession.